Manuscript of Kitab Sifat Dua Puluh: The Portrait of Moderate Islamic Theological Doctrines from Interior Borneo - Faizal Amin; Moh. Nor Ichwan (Jurnal Theologia, 2020)
The construction of religious moderation is not only derived from the context of practices but also the texts of its theological doctrines. Manuscripts of Kitab Sifat Dua Puluh from West Kalimantan is a primary source to study the basis of Islamic religious moderation in Interior Borneo. The texts of the manuscript are no longer presented as a copy of al-Sanūsī’s Umm al-Barāhīn but it has become a corpus that accommodates local genius and tradition. This article aims to examine the moderation of Islamic theological doctrine derived from the texts of the manuscript of twenty attributes of God. The texts of a manuscript considered as one of the sustainable best practices of South-East Asian localisations of Islam because it was one of the basic references for the local Dayak Muslim community learning Islam in interior Boneo. This article is based on the results of philological studies on the manuscript collection written by Abang Ahmad Tahir (1860-1945) in Kapuas Hulu, West Kalimantan, Indonesia.  The moderate Islamic theological doctrine in Abang Ahmad Tahir’s manuscript collection can be seen through three indicators namely the simplicity of the narrative articulation and arguments of the attributes of God, the synthesis of Islamic theological doctrine with Sufi doctrine, and the content of the text that gives no room for hate speech against local tradition and different systems of belief of the indigenous offspring of West Kalimantan.